Faktor-faktor Demografi yang Mempengaruhi Pertumbuhan Ekonomi di Indonesia - Dados Susilowati; Happy Adianita (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
One of the indicators used to see the success of development in an area is the level of economic growth. Economic growth is not only influenced by economic factors, but growth can be influenced by non-economic factors, one of which is demographic factors. This study aims to analyze the influence of demographic factors on economic growth in Indonesia in 2007-2022. The data in this study are secondary data taken from the Central Bureau of Statistics, using the multiple linear regression research method with the help of Eviews 12. The results show that partially the variable population growth has a positive and significant effect on economic growth, the labor force participation rate variable has a negative effect and not significant to economic growth and the dependency ratio variable has a negative and significant impact on economic growth in Indonesia in 2007-2022. Simultaneously the variables of population growth, labor force participation rate and dependency ratio have a significant impact on the growth of the economy in Indonesia in 2007-2022.